2019
DOI: 10.1002/ejoc.201900311
|View full text |Cite
|
Sign up to set email alerts
|

A Green Alternative for the Conversion of Arylboronic Acids/Esters into Phenols Promoted by a Reducing Agent, Sodium Sulfite

Abstract: Hydroxylation of arylboronic acids and arylboronic esters using sodium sulfite and oxygen as the source of ultimate oxidant proceeds rapidly in water under transition metal‐free conditions. This remarkable mild and environmentally benign protocol represents a green alternative to synthesize phenols using inexpensive starting materials in a simple methodology. This new application for sodium sulfite shows a wide tolerance of functional groups, and it is compatible with oxidizable functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Very recently, Schmidt and Argüello reported a sodium sulfite promoted conversion of aryl boronic acids/esters to phenols (Scheme ) . Taking advantage of the reducing property of Na 2 SO 3 , reactive oxygen species was generated in aqueous medium.…”
Section: Catalyst‐free Conversion Of Aryl Boronic Compounds To Phementioning
confidence: 99%
“…Very recently, Schmidt and Argüello reported a sodium sulfite promoted conversion of aryl boronic acids/esters to phenols (Scheme ) . Taking advantage of the reducing property of Na 2 SO 3 , reactive oxygen species was generated in aqueous medium.…”
Section: Catalyst‐free Conversion Of Aryl Boronic Compounds To Phementioning
confidence: 99%
“…Recently, several environmentally friendly methods have been reported to avoid the use of potentially toxic metal-catalysts. [18][19] However, in most cases, longer reaction times and complex reaction systems were necessary. Herein, we report a catalyst-free condition for the transformation of aryl boronic acids to substituted phenols by using H2O2 as oxidant and solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of phenols has received much attention in recent studies because of its importance as a starting material and structural constituent of pharmaceuticals, polymers, versatile intermediate building blocks [14] and natural products [15][16][17]. Mulakayala et al reported the preparation of phenols from aryl boronic acids by treatment with hydrogen peroxide in the presence of Amberlite IR-120 resin; the reaction was conducted at room temperature in the absence of an organic solvent [18].…”
Section: Introductionmentioning
confidence: 99%